Terompong Basic Tone Synthesis with Frequency Modulation Method - Pratama, I Gede Erwin Winata; Putri, Luh Arida Ayu Rahning (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 3 (2021): JELIKU Volume 9 No 3, Februari 2021, 2021)
Terompong is a type of gamelan in Bali Province. This gamelan is commonly used in traditional ceremonies in Bali, especially the Dewa Yadnya and Pitra Yadnya. The terompong are striking instruments, where the bat is made of wood. The terompong is also a two-octave musical instrument composed of 10-12 small metal gong blocks. The gong blocks are arranged parallel, which makes the gong difficult to carry and has to stay somewhere if someone want to play. Of course, with this situation people find it difficult to learn the terompong because they are quite large and heavy. This problem could be solved by replace the original terompong with synthetic terompong. The synthesis referred here the synthesis of sound. In performing sound synthesis, the method used is Frequency Modulation (FM). The result of the synthesis carried out where the difference between fundamental frequency of the original tone and the synthesis tone is almost close to zero. The sound produced almost follows the original sound, but it can't follow the sound of metal being hit with a wooden club.